On the economic essence concept innovation and innovation in land tenure - Tretyak, A.; Kolganova, I. (Land Management, Cadastre and Land Monitoring, 2017)
Transformation processes that take place at the present stage in Ukraine's economy, connected with the formation of innovative development model, which is directly based on obtaining of the new scientific results and their technological implementation in production, зproviding a real GDP increase is mainly due to the production and sale of high technology products. It is characterized by the presence of government policy and legislation designed to stimulate of innovation processes, the prevalence of intellectual nature of work on industrial and integrated technologies. Therefore, in performing the tasks to ensure the dynamic development of the economy's primary role is played by innovation and innovation activities.Innovative economy (knowledge economy, intellectual economy) – type of economy based on innovation stream, on constant technological improvement, in manufacturing and exporting of high technology products with a high added value and themselves technologies. It is assumed that this is mainly income creates intelligence of innovators and scientists, information sphere, rather than material production (industrial economy) and not the concentration of finance (capital).Innovative Economy includes six main components: education; science; human capital, including high quality of life and highly qualified specialists; innovation systemthat includes legislative framework and material components of the innovation system (technology transfer centers, business incubators, technology parks, technopolises, innovation centers, clusters, territory of development of high technology venture business etc.); innovative industry that implements innovations; favorable environment of functioning of scientific and educational system, work and life of innovators.The number of major components of an effective innovation economy in land management can be reduced to four: high-quality scientific and educational system in the broad definition; effective innovation system; an effective system of activity in sphere of land management, is able to produce innovative products; favorable environment for research and educational system.In the field of scientific innovation activities model of innovative land management should offer, first of all, capitalization of new knowledge and land use. Branch to a lesser extent should focus on inclusion directly in structure of implementing pilot projects of land management  and more – to stimulate interaction with the application and the market launch of scientific and technological developments, generate in this direction new approaches, that play a role  of of communication center in the chain «Science – real market of high technologies use and protection of land and other natural resources».Keywords: innovation, innovation activity, land management, innovative economy.